Evaluation of the Cooperative College-School Science Improvement Program to Prepare Teachers to Teach the DISCUS Program. - Bridges Jr., C. M.; Bingham, N. Eldred; Green, Martha M. (Science Education)
This study evaluates the Cooperative College-School Science Improvement Program to prepare teachers to teach the DISCUS Program. DISCUS Program is a junior science curriculum which was designed for and taught to underachieving students in the Duval County Public Schools in Florida. The Teacher Practices Observation Record, an instrument designed to enable an in classroom observer to collect data observing a teacher's actual teaching behavior, showed that the trained teachers generally provided more active student involvement, less external disciplinary control and more student-centered instruction.